Tahiti & French Polynesia - Brash, Celeste; Harrell, Ashley (Travel writer); Carillet, Jean-Bernard (Lonely Planet Global Limited, 2023)
Lonely Planet's Tahiti and French Polynesia is our most comprehensive guide that extensively covers all the region has to offer, with recommendations for both popular and lesser-known experiences. Swim in the sparklingly clear waters, hike to waterfalls, dive into coral wonderlands, then sip cocktails by the beach; all with your trusted travel companion.